Failures of non-melanoma skin cancer therapy - Włodarkiewicz, Adam; Sobjanek, Michał; Michajłowski, Igor; Warzecha, Anita (Dermatology Review/Przegląd Dermatologiczny, 2010)
Introduction. During three months of 2009, 177 patients with non-melanoma skin cancers (NMSCs) referred to the department for consultation and planning of therapeutic procedures were examined. The majority of them (131) presented recurrent or noncured neoplasms. Tumours were located in the head and neck region and 56.6% of them in areas of high risk of recurrence and metastases. Objective. To analyse the reasons for failure of the first treatment of non-melanoma skin cancers. Results. Treatment failures were observed most frequently in cases of basal cell carcinoma. In this group over 66% of tumours presented one or more clinical high-risk factors and 11% histopathological features of aggressiveness. Over 29% of all lesions were treated without histopathological verification of clinical diagnosis. Among patients with recurrence or uncured cancers 75% were treated by cryodestruction of the lesions. Surgical excision was performed in a small minority of cases and 52% of those tumours were not radically resected. Conclusions. Failures of the first treatment of cutaneous cancers causes significant difficulties in following surgical management, including reconstruction dilemmas as well as the necessity of complementary radiotherapy, especially in cases in which oncological “clearness” is difficult to achieve.